Pembuatan Solar Cell Menggunakan Transistor Jenis Npn Type 2n3055 Untuk Menghasilkan Tegangan 12 Volt - Wijaya, Zulfutra; , Hasyim Asy'ari, ST.MT (2017)
Energy is constantly increasing. The rapid energy every year is always progressing technology. These conditions will cause problems if the energy supply is less to make ends meet. Harnessing the potential of solar energy is an alternative to overcome the energy shortage occurs. Even the fossil material and natural gas can no longer suffice for a long time to renew the fossil material. The use of alternative energy is urgently needed because the resources readily available and environmentally friendly, resulting in pollution that little or almost nothing. One alternative power source that exists is the sun that will not be exhausted. The purpose of this research is the manufacture of solar cells using a Type 2N3055 NPN transistors generate egangan 12 Volt. This research method is the measurement of light intensity in real and measuring the output power of the solar cell. The materials used are Lux Camera application to measure the intensity of sunlight, multimeter is used to measure voltage and current. Tests conducted for 3 days, every day starting at 10:00 to 13:00 with the highest light intensity value occurs on the third day amounted to 19 261 Lux, while the output voltage high of Solar Cell 14:16 Volt, and the highest Flow 0:21 MA (Mili Amper). 2.9736 Watt produces the highest power.